2021
DOI: 10.1029/2021ja029752
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of IMF By Influences the Magnetotail Response to Solar Wind Forcing

Abstract: Magnetosphere-ionosphere dynamics are determined by the solar wind and interplanetary magnetic field (IMF) forcing and the system's response to that forcing. Arguably, the most important quantity in the solar wind forcing is the rate of opening of magnetic flux, or the reconnetion rate, on the dayside magnetopause. For several decades, coupling functions have been used to quantify the upstream solar wind forcing. Typically, coupling functions are proportional to the product 𝐴𝐴 𝐴𝐴 𝛼𝛼 𝐡𝐡 𝛽𝛽 𝑇𝑇 sin 𝛾… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Holappa et al. (2021b) noted that this By sign dependence is very strong in the winter hemisphere, but it is weak in the summer hemisphere, and is much stronger in the westward electrojet than in the eastward electrojet. Holappa and Buzulokova (2022) noted that the physical mechanisms of IMF By effects, which apply not only to auroral zone electron precipitation and ionospheric conductance but also to the fluxes of energetic magnetosphere protons and the growth rate of the ring current, are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Holappa et al. (2021b) noted that this By sign dependence is very strong in the winter hemisphere, but it is weak in the summer hemisphere, and is much stronger in the westward electrojet than in the eastward electrojet. Holappa and Buzulokova (2022) noted that the physical mechanisms of IMF By effects, which apply not only to auroral zone electron precipitation and ionospheric conductance but also to the fluxes of energetic magnetosphere protons and the growth rate of the ring current, are still not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Holappa et al. (2021b) noted that many studies using ground magnetometers, beginning with Friis‐Christensen and Wilhjelm (1975) and using polar‐orbiting satellites (Friis‐Christensen et al., 2017; Smith et al., 2017), have shown that auroral electrojets in the northern hemisphere winter are stronger in both hemispheres for By > 0 than for By < 0, and that in NH summer the dependence on the By sign is reversed. Holappa et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Holappa et al. (2023) and Kubyshkina et al. (2023) adopted 1 hr averaged IMF components spanning from 1981 to 2019 to investigate the IMF B x effect on AL index.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study by Holappa et al (2021b) found that the substorm onset latitude and the isotropic boundary latitude of energetic protons were both ~1Β°l ower during IMF By > 3 conditions than for smaller By, and that the substorm occurrence frequency was larger for small By. They suggested, consistent with the results of a resistive MHD study by Hesse and Birn et al (1990), that the magnetotail was more stable during conditions of large IMF By, requiring the magnetotail lobes and the polar cap to contain more flux to initiate a substorm compared to the situation when By was small.…”
Section: Amplitude Comparisonsmentioning
confidence: 92%